Measurement Of Aluminium Alloy 6061 Diameter Results Using Profile Projector - Jaja Miharja; Heru Santosa; Hery Adrial (Prodi Teknik Mesin, 2023)
The writing of this study was conducted to measure the circle of variations of aluminum alloy 6061 with a diameter of 20mm, 25mm and 30mm, respectively the speed on the CNC frais engine is different, among others, low speed 500 Rpm, medium speed 700 Rpm and high speed of 1000 Rpm. In addition, the results of frais CNC 3 Axis machine are validated using Profile Projector measuring tool that has a higher accuracy rate compared to other measuring instruments.The purpose of the study was to determine the effect of CNC engine speed with low, medium and high speeds on the dimensions of diameters of 20mm, 25mm and 30mm. and to find out the results of the deviation measure and accuracy of the hole work process by using frais CNC machine and Digital Caliper measuring instrument and Profile Projector.The result of this study was that the variation values of sample measurements using Varnier Caliper Digital and Profile Projector were heavily influenced by machine speed, and the result of the average deviation value was very pharmaceutical. Keywords: Measurement of aluminum alloy diameter 6061, frais CNC machine Results 3 Axis with speeds of 500, 700, and 1000 Rpm, with Profile Projector measurement